Coating composition
Patent Information
- Application Number
- JP2023123735
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-03-11
Smart Images

Figure 2025032051000001 
Figure 2025032051000002 
Figure 2025032051000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a lubricant coating composition having excellent sliding and insulating properties, and a sliding member having a coating film formed from the coating composition. [Background technology]
[0002] Insulating coatings are applied onto the metallic surfaces of many industrial materials, but when the coatings are used on sliding members, such as stators for rotors or windings in motors, the surfaces of such sliding members are frequently rubbed against other parts, so the coatings tend to be damaged.
[0003] In order to increase the abrasion resistance of a coating film, a coating composition containing hard particles is known. For example, Patent Document 1 discloses a coating composition containing a binder resin, a lubricant and hard particles.
[0004] However, it is difficult to obtain an insulating coating that has both excellent sliding properties and high durability. When the amount of lubricant or hard particles in the coating composition is increased, the amount of binder resin is relatively decreased, and thus the insulating properties of the coating film are reduced. In addition, other resin properties such as adhesive properties are also reduced. Therefore, there is still a need for an insulating coating that has excellent sliding properties as well as high durability.
[0005] When a coating is applied to a substrate, "blistering" or "bubbling" is observed on the surface of the coating. In this specification, the words "blistering" and "bubbling" are used synonymously. Blistering refers to the formation of air bubbles under or in the coating film and is known as a coating defect. One assumed mechanism of blister formation is that when a coating is applied to a porous or rough substrate, air trapped in the pores of the substrate or in the grooves of the rough substrate is sealed by the applied coating. If the coating composition is over-agitated, air is also included in the coating composition. Normally, such air evaporates together with the solvent during the curing process, but if the surface of the coating film is first dried and for some reason a skin layer is formed on the coating surface, such air cannot evaporate and forms blistering. If the thickness of the coating film is increased or a rough substrate is used, blisters are frequently observed and cause problems.
[0006] Usually, defoamers are added to the coating composition to reduce bubbles in the coating composition, but such defoamers cannot completely suppress the blister formation during the curing process of the coating composition. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2020-090562 A Summary of the Invention
[0008] The specific formulation of the coating composition, especially the volume ratio of binder resin to solid particles / lubricant, improves both the sliding properties and durability of the coating composition. Furthermore, a certain amount of epoxy resin acts to significantly reduce blister formation, even when the coating film is formed on a rough surface.
[0009] Thus, one aspect of the present invention is (A)(i) at least one binder resin comprising a resin selected from the group consisting of polyamideimide, polyimide, and benzocyclobutene; (B) a solid lubricant, and (C) optionally, another solid particle other than the solid lubricant; The coating composition comprises the above-mentioned compound, and the volume ratio of [(B)+(C)] / (A) is 0.1 to 0.3.
[0010] Another aspect of the present invention is a coating film prepared from the coating composition.
[0011] Furthermore, another aspect of the present invention is a sliding member having the above coating film.
[0012] The present invention also relates to a method for forming the coating film on a sliding member. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] <Compound> A) Binder resin (i) The binder resin used in the present invention is a resin that forms a lubricating film as an insulating resin and functions as a binder to support the solid lubricant described below. Examples of resins that can be used include polyamideimide (PAI), polyimide (PI), benzocyclobutene (BCB), phenolic resin, polyamide, polybenzimidazole, polyphenylsulfonate, and polyetheretherketone, and one or more of these. Preferably, the binder resin contains polyamideimide, polyimide, and benzocyclobutene. More preferably, the binder resin contains polyamideimide. The content of the binder resin is 60 to 95% by weight, preferably 70 to 90% by weight, based on the weight of the solid content of the entire coating composition.
[0014] (ii) Epoxy resin The binder resin can optionally include an epoxy resin. When the binder resin includes an epoxy resin, blistering can be significantly reduced and the surface of the coating film can be smoothed. Without being bound by theory, the inventors believe that the epoxy resin can soften the skin layer of the coating composition or slow down the formation rate of the skin layer. As a result, the air bubbles inside the coating composition can easily evaporate together with the solvent, and do not generate blisters during the curing process. The amount of the epoxy resin is usually 1 to 40, preferably 10 to 30, and more preferably 15 to 25 parts by weight based on 100 parts by weight of the binder resin (A)(i).
[0015] The epoxy resin is not particularly limited, and one or more types including bisphenol-based epoxy resins, amine-based epoxy resins, phenol novolac-based epoxy resins, cresol novolac-based epoxy resins, resorcinol-based epoxy resins, phenol aralkyl-based epoxy resins, naphthol aralkyl-based epoxy resins, dicyclopentadiene-based epoxy resins, epoxy resins having a biphenyl skeleton, isocyanate-modified epoxy resins, tetraphenylethane-based epoxy resins, triphenylmethane-based epoxy resins, and fluorene-based epoxy resins may be selected and used.
[0016] Generally, bisphenol-based epoxy resins are epoxy resins in which two phenolic hydroxyl groups of a bisphenol compound are glycidylated, and examples thereof include bisphenol A type, bisphenol F type, bisphenol AD type, bisphenol S type, or halogen or alkyl substitutes, hydrogenated products, dimer acid modified products, etc. Furthermore, bisphenol-based epoxy resins are not limited to monomers, and polymers having multiple repeating units can also be preferably used.
[0017] Examples of commercially available bisphenol A epoxy resins include jER® 825, 828, 834, 1001, 1002, 1003, 1003F, 1004, 1004AF, 1005F, 1006FS, 1007, 1009, and 1010, which are products of Mitsubishi Chemical Corporation. Examples of brominated bisphenol A epoxy resins include jER® 505, 5050, 5051, 5054, and 5057, which are products of Mitsubishi Chemical Corporation. Examples of commercially available hydrogenated bisphenol A epoxy resins include ST5080, ST4000D, ST4100D, and ST5100, which are products of Nippon Steel Chemical Co., Ltd.
[0018] B) Solid lubricants The coating compound of the present invention contains one or more solid lubricants (B). The solid lubricant can provide sliding properties to the coating film formed from the composition. Examples of solid lubricants that can be used include polytetrafluoroethylene (PTFE), polyamide (PA), polyether ether ketone (PEEK), polyethylene (PE), polypropylene (PP), and acrylic resin. Preferably, the solid lubricant contains PTFE. The amount of the solid lubricant is usually 10 to 50 parts by mass, preferably 20 to 40 parts by mass, relative to the binder resin (A).
[0019] Furthermore, the amount of the solid lubricant is determined so as to satisfy the condition that the volume ratio of [(B)+(C)] / (A) is 0.1 to 0.3, as disclosed below.
[0020] (C) Other solid particles The coating composition of the present invention optionally contains, in addition to the solid lubricant (B), one or more other solid particles.
[0021] One example of other solid particles is hard particles. Hard particles can provide abrasion resistance to the coating film formed from the composition. Hard particles refer to particles with a new Mohs hardness of more than 4, preferably more than 9. Hard particles include tungsten carbide, titanium nitride, zirconia, alumina, and silicon carbide.
[0022] Examples of other solid particles include: coloring materials, including colorants (inorganic and organic), such as pigments; carbon (e.g., carbon black, fullerenes, and carbon nanotubes); ultraviolet absorbing (or blocking) materials, including metal oxides (or metal oxide particles), such as titanium oxide and zinc oxide; fibrous materials (e.g., glass fibers, carbon fibers, metal fibers and whiskers); ferromagnetic materials, e.g., ferromagnetic metals (powders) such as iron, cobalt, and nickel; ferromagnetic alloys (powders) such as magnetite and ferrite; ferromagnetic metal oxides, such as magnetic iron oxide (powders); metal hydroxides (e.g., aluminum hydroxide); metal salts (e.g., metal sulfates and carbonates, such as calcium carbonate, metal phosphates, such as calcium phosphate and titanium phosphate); mica; calcium silicates; and silicates, such as bentonite, zeolites, talc, and montmorillonite.
[0023] When the coating composition contains other solid particles, the amount of such solid particles is usually from 0.1 to 5 parts by mass, preferably from 0.2 to 1.0 part by mass, based on the binder resin (A).
[0024] The key to the present invention is that the volume ratio of [(B)+(C)] / (A) is 0.1-0.3. When the volume ratio is within this range, a coating film with both excellent sliding and insulating properties is obtained. When the ratio is less than 0.1, the amount of solid lubricant is not sufficient, and therefore the COF (coefficient of friction) of the coating film is high. As a result, the coating film wears out in a short time. On the other hand, when the ratio is greater than 0.3, the adhesion between the coating film and the substrate is low, or the coating film cannot hold the solid lubricant well, and therefore the coating film wears out in a short time. Furthermore, the voids between the binder resin and the solid lubricant / other solid particles are increased, and therefore the insulating properties of the coating film are poor. Such voids can be observed by SEM analysis after vertical / horizontal cutting of the coating film.
[0025] (D) Solvent The coating compounds described herein can further include solvents and liquid additives. Examples of solvents include ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; esters such as methyl acetate and ethyl acetate; aromatic hydrocarbons such as toluene and xylene; organic halogen compounds such as methyl chloroform, trichloroethylene, and trichlorotrifluoroethane; N-methyl-2-pyrrolidone (NMP); N-ethyl-2-pyrrolidone (NEP); 1,3-dimethyl-2-imidazolidinone (DMI); γ-butyrolactone (GBL); 3-methoxy-N,N-dimethylpropanamide (MPA); methylisopyrrolidone (MIP); dimethylformaldehyde (DMF); dimethylacetaldehyde (DMAC) and 1-butyl-2-pyrrolidone (NBP). The solvent may be one or a mixture of two or more. Particularly preferred solvents are NEP, DMI, GBL, and MPA.
[0026] (E) Other ingredients The coating compound described herein may further include liquid additives different from the solid particles (C). The liquid additives include; UV absorbers, light stabilizers, antioxidants, thermal polymerization inhibitors, flattening agents, defoamers, thickeners, anti-settling agents, infrared absorbers, fluorescent whitening agents, dispersants, antistatic agents, anti-fogging agents, coupling agents and thixotropic agents. The thixotropic agents include fillers such as bentonite, calcium carbonate, kaolin, and clay, such as, polymerized linseed oil, castor oil wax, polyolefins, silica gel, aluminum organic acid salts, cellulose, amide wax, and polyamide-based thixotropic agents. Polymer-type flattening agents such as acrylic acid-based and silicone-based flattening agents, polyoxyalkylene fatty acid alkanolamide derivatives, etc. may also be used.
[0027] <Method for forming a coating film on a sliding member> The method includes three steps, namely, (a) preparing the coating composition disclosed above, which includes (A), (B) and, optionally, (C); (b) applying the coating composition onto the surface of the sliding member; and thereafter, (c) curing the coating composition to form a coating film on the surface of the sliding member.
[0028] [Process (a)] The coating composition comprising (A), (B) and, optionally, (C) can be prepared by mixing the composition using a propeller mixer, a rotary / swirl mixer, or other mixing device. A solvent can be added to obtain a coating composition having a viscosity suitable for coating the composition on a sliding member.
[0029] [Step (b)] The coating composition is applied onto the surface of the sliding member by dipping, spin coating, flow coating, spraying, bar coating, gravure coating, roll coating, blade coating, screen printing, air knife coating and other methods. The thickness of the coating film is not particularly limited, but is preferably 1 to 100 μm, more preferably 40 to 80 μm. Optionally, the sliding member can be pretreated before applying the coating composition.
[0030] [Process (c)] The coated composition is cured to form a coating film on the surface of the sliding member. Typically, heat curing is performed by heating in an oven or any other device. During heat curing of the applied composition, the solvent in the composition can be removed in a first stage of heating, and the composition can be cured by a crosslinking reaction in a second stage of heating. For example, the first stage of heating may be performed at 60-100°C for 5-30 minutes, followed by a second stage of heating at 180-250°C for 20-120 minutes.
[0031] <Sliding parts> The coating composition is useful for insulating coatings on metal surfaces of sliding members. Examples of such sliding members include inner or outer rings for bearings, bearing shafts, EV stator cores, battery trays, PCUs (power control units) and housings (including inverter cases and DC / DC converters).
[0032] This coating composition can be used on the metal surface of a sliding member even if the metal surface of the sliding member is rough, for example, the surface roughness is 10 μm or more. The surface roughness (Ra) is defined as the arithmetic average roughness based on JIS B0601 (2001). The Ra of the surface of the sliding member to be coated may be preferably 0.1 to 20 μm, or the Ra of the surface of the member may be 1 to 10 μm. Usually, when the surface of the member is rough, it is difficult to obtain a smooth coating surface without blistering. This coating composition, particularly a coating composition containing an epoxy resin, can provide a smooth coating surface without blistering. EXAMPLES
[0033] material 1. Binder resin [A] PAI-A: Polyamide-imide resin dissolved in NEP (solid content is 35% by weight) (specific gravity: 1.4) PAI-B: Polyamide-imide resin dissolved in GBL (solid content is 36% by weight) (specific gravity: 1.4) PAI-C: Polyamide-imide resin dissolved in MPA (solid content is 35% by weight) (specific gravity: 1.4) PI-A: Polyimide resin dissolved in NEP (solid content is 20% by weight) (specific gravity: 1.4) Epoxy-A: Epoxy resin, product name is jER828, bisphenol A type epoxy resin, available from Mitsubishi Chemical (specific gravity: 1.4) Epoxy-B: Epoxy resin, product name jER1007, bisphenol A type epoxy resin, available from Mitsubishi Chemical (specific gravity: 1.4) BCB: Benzocyclobutene resin dissolved in mesitylene, Cyclotene 3022-63, available from DuPont, 63% solids by weight. (Specific gravity: 1.4) Phenolic: Phenolic resin, product name TD-2495, available from DIC Corporation. (Specific gravity: 1.4)
[0034] 2. Solid lubricant [B] PTFE-A: Spherical polytetrafluoroethylene resin microparticles (specific gravity: 2.0) with a median diameter of 3 to 7 μm as measured by laser diffraction scattering particle size distribution measurement. PTFE-B: Spherical polytetrafluoroethylene resin microparticles (specific gravity: 2.0) with a median diameter of 4 to 8 μm as measured by laser diffraction scattering particle size distribution measurement. MoS2: MoS2tech fine, available from Climax Molybdenum Company, molybdenum disulfide microparticles with a median diameter of 4-6 μm as measured by laser diffraction scattering particle size distribution measurement (specific gravity: 4.8) Gra-A: Graphite UF-2, available from Graphit Kropfmuhl GmbH, graphite particles with a median diameter of 4-5.5 μm as measured by laser diffraction scattering particle size distribution measurement (specific gravity: 2.2)
[0035] 3. Solid Additives [C] CB: Carbon Black MA-100, available from Mitsubishi Chemical, with a median diameter of 1-2 μm as measured by laser diffraction scattering particle size distribution measurement (specific gravity: 1.7)
[0036] 4. Solvent [D] NEP: N-Ethyl-2-pyrrolidone, available from Maruzen Chemical GBL: gamma-butyrolactone, available from Mitsubishi Chemical MPA: 3-Methoxy-N,N-dimethylpropanamide, available from KJ Chemicals Xylene: Xylene, available from Kyoe iChemical DAA: Diacetone alcohol, available from Sankyo Chemical MEK: Methyl ethyl ketone, available from Sankyo Chemical
[0037] 5. Other ingredients [E] Defoamer: Xiameter OFX-0230 Fluid, available from Dow chemical
[0038] (Examples 1 to 15) The components disclosed in Tables 1-4 were mixed in a rotary / gyratory mixer at room temperature. The mixture was diluted with a solvent to adjust the solid concentration to about 23-26% by weight. The coating composition was coated on a test sample (material: steel plate, cold, commercial (SPCC)-SB plate, size: 150 mm x 70 mm x 0.6 mm, surface roughness Ra = 0.1) by spray coating. The thickness of the spray-coated layer is 0.07 mm. The test sample was then placed in an oven at 230 °C for 60 minutes to evaporate the solvent and harden. The thickness of the coated film was 0.05 mm. The following evaluation tests were performed.
[0039] (analytical method) Dielectric Strength: The dielectric strength of the coated SPCC-SB plate was measured by using HIOKI's automatic voltage insulation tester 3153 according to ASTM D149-09 (JISC2010-1). Trigger to leakage current 0.5mA, step up by 0.5kV (AC), hold for 20 seconds, and judge whether OK or not. If OK, change the voltage to 1.0kV, hold for 20 seconds, and continue until failure occurs.
[0040] Durability: Ring-on-plate coated with EFM-III-1010 available from Orientec Corporation was performed. Rotation speed: 2000 rpm, load 1000N until seizure.
[0041] Surface roughness: Surface roughness was measured according to JIS 2001:2013. A surface roughness profiler Surfcom 1400D available from Accretech was used. Measurement speed for the needle: 0.6 mm / sec.
[0042] Blisters: The appearance of the coated SPCC-SB was observed under an Olympus DP28 microscope to confirm the presence of blisters.
[0043] [Table 1] In Tables 1 to 4, the values are given as parts by weight for each component. *The [(B)+(C)] / (A) volume ratio is calculated by converting units from weight to volume using the specific gravity of each component, e.g., Example 2: 0.11=(8 / 2.0+8 / 2.0+0.5 / 1.7) / 100 / 1.4. **Durability (minutes): Preferably longer than 5 minutes. **Blisters: ◯ indicates the absence of blisters, × indicates the presence of some blisters.
[0044] [Table 2]
[0045] [Table 3]
[0046] [Table 4]
Claims
1. (A)(i) at least one binder resin comprising a resin selected from the group consisting of polyamideimide, polyimide and benzocyclobutene; (B) a solid lubricant, and (C) optionally, solid particles other than the solid lubricant; wherein the volume ratio of [(B)+(C)] / (A) is 0.1-0.
3.
2. The coating composition of claim 1 , wherein the solid lubricant is polytetrafluoroethylene.
3. 10. The coating composition of claim 1, wherein the solid particles are carbon black.
4. The coating composition according to claim 1 , wherein the binder resin (A) further comprises, in addition to (i), (ii) an epoxy resin.
5. 5. The coating composition of claim 4, wherein the weight ratio of (A)(i) / (A)(ii) is from 100 / 1 to 100 / 40.
6. A coating film made from the coating composition according to claim 1, having a dielectric strength of 50 kV / mm or more.
7. Before hardening, (A)(i) at least one binder resin comprising a resin selected from the group consisting of polyamideimide, polyimide and benzocyclobutene; (B) a solid lubricant, and (C) optionally, solid particles other than the solid lubricant; a volume ratio of [(B)+(C)] / (A) being 0.1 to 0.3, and the coating film having a dielectric strength of 50 kV / mm or more.
8. Before hardening, (A) at least one binder resin comprising: (i) a resin selected from the group consisting of polyamideimide, polyimide, and benzocyclobutene; and (ii) an epoxy resin; (B) a solid lubricant, and (C) optionally, solid particles other than the solid lubricant; A sliding member having a coating film comprising: a coating film having a volume ratio of (B)+(C) / (A) of 0.1 to 0.3; and a surface of the coating film having an Ra of 1 or less as measured in accordance with JIS 2001:2013.
9. 9. The sliding member according to claim 8, wherein a surface of the sliding member to be coated with the coating film has an Ra of 10 or more as measured in accordance with JIS 2001:2013.
10. 9. The sliding member according to claim 7 or 8, which is in the form of an inner or outer ring for a bearing, a bearing shaft, an EV stator core, a battery tray, a power control unit, a housing for an inverter case, or a DC / DC converter.
11. A method for forming a coating film on a sliding member, comprising the steps of: (a) preparing a coating composition, (A)(i) at least one binder resin comprising a resin selected from the group consisting of polyamideimide, polyimide and benzocyclobutene; (B) a solid lubricant, and (C) optionally, solid particles other than the solid lubricant; preparing a coating composition comprising: (b) applying the coating composition onto a surface of a sliding member; and then (c) curing the coating composition to form a coating film on the surface of the sliding member; A method comprising:
Citation Information
Patent Citations
Composition, coating film formed using the same, sliding member having said coating film, and manufacturing method thereof
JP2020090562A